2013
DOI: 10.1016/j.biomaterials.2013.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Affibody modified and radiolabeled gold–Iron oxide hetero-nanostructures for tumor PET, optical and MR imaging

Abstract: A highly monodispersed hetero-nanostructure with two different functional nanomaterials (gold (Au) and iron oxide (Fe3O4, IO)) within one structure was successfully developed as Affibody based trimodality nanoprobe (positron emission tomography, PET; optical imaging; and magnetic resonance imaging, MRI) for imaging of epidermal growth factor receptor (EGFR) positive tumors. Unlike other regular nanostructures with a single component, the Au-IO hetero-nanostructures (Au-IONPs) with unique chemical and physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
92
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 37 publications
3
92
0
2
Order By: Relevance
“…However, only limited data regarding the in vivo application of gold at magnetite hybrid particles are available, especially regarding their cellular uptake and in vivo imaging abilities. Yang et al previously developed Au@Fe 3 O 4 hetero-nanostructures as affibody based trimodality nanoprobes (positron emission tomography, PET; optical imaging;and magnetic resonance imaging, MRI) for imaging of epidermal growth factor receptor EGFR) positive tumors and have shown that they provided high specificity, sensitivity, and excellent tumor contrast for both PET and MRI imaging[73]. In our study, nanoparticles by MRI 24 h post injection and by atomic adsorption spectroscopy in mice 48 h post injection.…”
mentioning
confidence: 98%
“…However, only limited data regarding the in vivo application of gold at magnetite hybrid particles are available, especially regarding their cellular uptake and in vivo imaging abilities. Yang et al previously developed Au@Fe 3 O 4 hetero-nanostructures as affibody based trimodality nanoprobes (positron emission tomography, PET; optical imaging;and magnetic resonance imaging, MRI) for imaging of epidermal growth factor receptor EGFR) positive tumors and have shown that they provided high specificity, sensitivity, and excellent tumor contrast for both PET and MRI imaging[73]. In our study, nanoparticles by MRI 24 h post injection and by atomic adsorption spectroscopy in mice 48 h post injection.…”
mentioning
confidence: 98%
“…Recently, associated research works have been mainly focused on dynamic imaging of the extracellular section of EGFR through imaging radiolabeled monoclonal antibodies, affibody or some substances in real time in vivo. [7][8][9][10] They can only reflect the expression level of EGFR but not EGFR mutational status, however, it remains unresolved for EGFR TKI resistance and EGFR mutation in clinical practice. On the other hand, increasing attention has been paid onto the use of radionuclides-labeled small molecule TKIs to identify EGFR mutation in vivo, such as 18 F, 11 C, and 64 Cu, etc.…”
mentioning
confidence: 99%
“…Nowadays, lots of literatures report the possibility of multimodality molecular imaging using nanoprobes, which supports the notion that clinical translation of this technology will be feasible in the near future [7,9,10]. Hence, the purpose of this review is to provide readers with a current update of multimodality molecular imaging of cardiovascular disease based on nanoprobes, which focus on six important aspects of cardiovascular diseases, including atherosclerosis, thrombosis, myocardial infarction and postinfarction remodeling, angiogenesis, apoptosis and cardiac stem cell-based therapy.…”
Section: Introductionmentioning
confidence: 82%